Performance and value creation at United Kingdom's airports using fsQCA - Romero, J.; Lafont, J.; Tafur, Javier; Eguren, S. (Elsevier, 2016)
© 2015 Elsevier Inc.International airports struggle to succeed in a highly competitive market with entrants bringing different business models, creating new hubs, and competing with traditional leading airports. In addition, privatization has key role in infrastructure funds and sovereign participates in its shareholding structure. This research focuses on the United Kingdom, where privatization of airports has a longer tradition, and analyzes in two phases the key factors that have an influence on their value creation in airports. First, the study analyzes the influence of the key factors governance, airlines, revenue structure, passengers, and strategy. In the second stage, using complementary data and fuzzy-set QCA, this study analyzes the effect of the key factors on economic success of the airport. This study concludes that diversification does not play a dominant role in large airports. However, airport type and performance, both economic and operational, are relevant. Future research should consider the effect of regulation, competition, and geopolitical factors.